2017
DOI: 10.1016/j.contraception.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrauterine contraception on the vaginal microbiota

Abstract: Objectives There have been conflicting reports of altered vaginal microbiota and infection susceptibility associated with contraception use. The objectives of this study were to determine if intrauterine contraception altered the vaginal microbiota and to compare the effects of a copper intrauterine device (Cu-IUD) and a levonorgestrel intrauterine system (LNG-IUS) on the vaginal microbiota. Study Design DNA was isolated from the vaginal swab samples of 76 women using Cu-IUD (n=36) or LNG-IUS (n=40) collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
(46 reference statements)
3
24
0
3
Order By: Relevance
“…The lack of change between the pre-IUD phase and IUD phase is consistent with recently published work in humans, although the human study did not extend to after IUD removal [9]. The mechanism behind the change in vaginal microbiota after IUD removal is unclear, as is the biological significance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The lack of change between the pre-IUD phase and IUD phase is consistent with recently published work in humans, although the human study did not extend to after IUD removal [9]. The mechanism behind the change in vaginal microbiota after IUD removal is unclear, as is the biological significance.…”
Section: Discussionsupporting
confidence: 82%
“…temperature, weight, menstrual cycle, discharge) and no changes in the vaginal microbiota attributable to Cu-IUD insertion and long-term use; however, we did find a slight but statistically significant alteration of the vaginal microbiota after Cu-IUD removal. The baboon recapitulates data and reports from human patients receiving a Cu-IUD: transcervical insertion is successful, no physiologic changes are observed while using the Cu-IUD, and insertion and use do not significantly affect the vaginal microbiota [9]. As we have demonstrated with the LNG-IUS in the baboon, we conclude that the olive baboon is a feasible model system for Cu-IUD studies.…”
Section: Discussionsupporting
confidence: 80%
“…Daily intravaginal progesterone suppository is considered an alternative option if access to 17‐OHP‐C is limited . The literature on whether progestogens have an effect on the vaginal microbiome is conflicting . Progesterone has known antibacterial, immunomodulatory, and anti‐inflammatory properties, with demonstrated effects on dendritic cells, macrophages, T‐cells, B‐cells, and cytokine release .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The literature on whether progestogens have an effect on the vaginal microbiome is conflicting. [17][18][19][20][21] Progesterone has known antibacterial, immunomodulatory, and anti-inflammatory properties, [22][23][24] with demonstrated effects on dendritic cells, macrophages, T-cells, B-cells, and cytokine release. [25][26][27][28][29][30][31] Animal models have demonstrated that intravaginal progesterone has local anti-inflammatory effects at the maternalfetal interface and the cervix.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the vaginal microbiota is distinct from other body sites and contains types of bacteria that seem specific to the vagina [5]. For example, the vaginal microbiota is often dominated by specific types of Lactobacillus , most commonly L. crispatus and L. iners [6, 7]. Vaginal Lactobacillus sp.…”
Section: Introductionmentioning
confidence: 99%